Daily Self-Monitoring of Body Weight, Step Count, Fruit/Vegetable Intake and Water Consumption: A Feasible and Effective Long-Term Weight Loss Maintenance Approach - Akers, Jeremy D. (2012)
Maintenance of weight loss remains a challenge for most individuals, thus practical and effective weight loss maintenance (WTLM) strategies are needed. A two-group (WEV versus WEV+) 12-month WTLM intervention trial was conducted (June 2007–February 2010) to determine the feasibility and effectiveness of weight loss maintenance intervention for older adults using daily self-monitoring of body weight, step count, fruit/vegetable intake and water consumption. Forty weight-reduced (mean weight lost = 6.7 ± 0.6 kg; BMI 29.2 ± 1.1 kg/m(2)) individuals aged 63 ± 1 yrs, who had previously participated in a 12-week randomized controlled weight loss intervention trial, were instructed to record daily body weight (Weight), step count (Exercise), and fruit/vegetable intake (Vegetable). Experimental group (WEV+) participants were also instructed to consume 16 floz of water before each main meal (i.e., three times daily), and to record daily water intake. Outcome measures included weight change, diet/physical activity behaviors, theoretical constructs related to health behaviors, and other clinical measures. Statistical analyses included growth curve analyses and repeated measures ANOVA. Over 12 months, there was a linear decline in weight (β = −0.32, P < 0.001) and a quadratic trend (β = 0.02, P < 0.01) over time, but no group difference (β = −0.23, P = 0.08). Analysis of the 365 days of self-reported body weight for each participant determined that weight loss was greater over the study period in WEV+ than WEV, corresponding to weight changes of −0.67 kg and 1.00 kg respectively, and an 87% greater weight loss (β = −0.01, P < 0.01). Overall compliance to daily tracking was 76 ± 5%. Daily self-monitoring of weight, physical activity, and fruit/vegetable consumption is a feasible and effective approach for maintaining weight loss for 12 months, and daily self-monitoring of increased water consumption may provide additional WTLM benefits.